Mapping the edge - Dunant, Sarah 1950- (Random House, 2001)
"Anna, a self-sufficient and reliable single mother, packs her bags one day for a short vacation to Italy. She leaves her beloved six-year-old daughter, Lily, at home in London with good friends. But when Anna doesn't return, everyone begins to make excuses until the likelihood that she might not come back becomes chillingly clear. And the people who thought they knew Anna best realize they don't know her at all." -- Jacket.
Keywords: British -- Italy -- Fiction; Missing persons -- Fiction; Mothers and daughters -- Fiction; Single mothers -- Fiction; Italien; Florence (Italy) -- Fiction; London (England) -- Fiction; Domestic fiction; Psychological fiction